Pancreatic Metastasis from Colorectal Cancer - Belluomini, Mario Antonio; Napoli, Niccolò; Kauffmann, Emanuele Federico; Gennai, Andrea; Costa, Francesca; De Lio, Nelide; Boggi, Ugo (JOP. Journal of the Pancreas, 2012)
Context Pancreatic metastases are rare (2% of all pancreatic carcinomas). Very few cases about surgical treatment of colorectal cancer metastases to the pancreas are reported. Case report We report a case of single colorectal cancer metastasis to the pancreas managed by distal splenopancreatectomy in a patient undergone to left hemicolectomy for the primary tumor eight years before and to middle lung lobectomy for metastasis one year before. A 61-year-old asymptomatic woman with a history of colorectal cancer was admitted to our department after that during the oncological imaging follow-up a thoracic-abdominal contrast-enhanced computed tomography (CT) demonstrated a single 25 mm hypodense lesion in the pancreatic tail. She also presented high levels of CEA (61.7 ng/mL) and CA 19-9 (82.9 U/mL) before the admission. Eight years before the patient underwent to left hemicolectomy for a B2-Dukes classification colorectal cancer. The resected margins were free of tumor and no regional lymph nodes were positive. One year before the patient underwent to a lung lobectomy for a single 30 mm pulmonary metastases. Considering history and imaging findings, the pancreatic lesion was suspected a colorectal cancer metastasis. A distal splenopancreatectomy was performed. The patient was discharged in healthy conditions. Final pathology disclosed the pancreatic lesion was a colorectal cancer metastasis (CD20+, CK7-) with infiltration of the peri-pancreatic adipose tissue. The resected margins were free of tumor and no lymph nodes were metastasized. The patient is still alive. Conclusion Metastases to the pancreas are commonly considered rare, especially those from colorectal cancer. The improvement of imaging techniques has led to an increase of diagnoses and surgical procedures for metastases to the pancreas. Secondary tumors may be considered in the differential diagnosis of primitive pancreatic lesions. The diagnosis may be facilitated by clinical history and serum markers assessment. Metastatic colorectal cancer to the pancreas is an indication for pancreatic resection to increase the overall survival and, as palliative procedure, to treat symptoms like jaundice and pain.